The Development of the Waqf Zurri Model Through Family Business Cooperatives - Muhammad Hamizan Bin Ab Hamidi; Madya Dr. Mohd Afandi Bin Mat Ranii; Dr. Afiffudin Bin Mohammed Noor; Dr. Mohamad Khairul Izwan Rifin; Dr. Mohd Syakir Bin Mohd Taib; 'Adnin Binti Ibrahim; Dr. Md Yazid Ahmad (International Journal of Educational Excellence and Innovation, 2024)
Waqf zurri is a transactional asset that is unique in Islam. It will appear as a form of devotion to Allah and social responsibility to the community. Waqf zurri has a high socio-economy value to develop the community. This paperwork will discuss the development waqf zurri model through family co-operatives. This paperwork will include an inquiry about the development of waqf zurri and potential growth, as well as the benefits. This research uses qualitative methods, informational research to collect data on waqf and field work that involve interview swith important vital people to gettheessential and primary information from those directly involved with the development of waqf zurri. Waqf zurri is crucial in providing a broader perspective of the process and characteristics of family waqf. It will help the public better comprehend the family waqf to practice it properly. It can be from a concise review of related studies that the development and sustainability of family waqf depend on all itsaspects and characteristics. The result of this study will give awareness, total or quantity of waqf land especially for family waqf, so it will not become less parallel to the government, intends to make asset of waqf as the centre line for the economic development of Muslim in Malaysia. Research shows that waqf zurri has its speciality to ensure continuous benefits to the family. Good development of waqf zurri is crucial to make sure that the assets developed and the benefits from them can continue to grow for the use of the community.